The Influence of Store Location, Brand Image, and Service Quality on Purchase Decisions - Syamtya Maharika Laurensya; Wahna Widhianingrum; Eka Destriyanto Pristi Ayuningtyas (Jurnal Indonesia Sosial Sains, 2025)
UMKM are the spearhead of a country's economy. Reyogfoody is one of the UMKM in Ponorogo City that provides a variety of food menus that are popular with young people by implementing a takeaway service system to improve service quality. However, with the limitation of employees that are not proportional to the number of orders, this causes problems with service quality, namely the wrong orders made. This study aims to analyze the influence of the location of the store, brand image and service quality on consumer purchase decisions in UMKM Reogfoody. This study implements a quantitative approach with a random sampling technique with a total of 96 respondents. The data collection technique used was in the form of a questionnaire which was then tested with multiple linear regression. The results of this study show that brand image and service quality have a positive and significant effect on purchase decisions. Meanwhile, the location of the store does not have a positive and significant influence.